Hydration state diagnosis in fractal flow-field based polymer electrolyte membrane fuel cells using acoustic emission analysis. (15th September 2020) - Bethapudi, V.S.; Hack, J.; Trogadas, P.; Hinds, G.; Shearing, P.R.; Brett, D.J.L.; Coppens, M.-O.
Highlights: Design, development and testing of two different configurations of fractal PEMFCs. Evaluation of the hydration state of fractal PEMFCs via acoustic emission method. Performance diagnosis of fractal PEMFCs using acoustic emission analysis. Correlation of acoustic emission analysis with conventional electrochemical studies. Abstract: Techniques for evaluating water management are critical to diagnose the performance of polymer electrolyte membrane fuel cells (PEMFCs). Acoustic emission as a function of polarisation (AEfP) has been recently introduced as a non-invasive, non-destructive method to analyse the water generation and removal inside a PEMFC during polarisation. AEfP was shown to provide unique insight into water management within a conventional PEMFC and correlating it to cell performance. Here, AEfP is used to characterise the performance of fractal PEMFCs by evaluating the hydration conditions inside them. This is achieved by probing the water dynamics inside two different fractal flow-field based PEMFCs, namely 1-way and 2-way fractal PEMFCs, and measuring the corresponding acoustic activity generated from them. AEfP is performed on the fractal PEMFCs under relatively humid (70% RH) and fully humidified (100% RH) reactant relative humidity (RH) conditions. Flooding in the 2-way fractal PEMFC, as opposed to the 1-way fractal PEMFC, is demonstrated under different operating conditions by the relatively higher acoustic activity it generates. Corroborating evidence of flooding in the 2-way fractal flow-field under different conditions is provided by its polarisation curves, impedance tests and galvanostatic (current hold) measurements.